2024
DOI: 10.24084/repqj09.609
|View full text |Cite
|
Sign up to set email alerts
|

Meat and Bone Meal as a Renewable Energy Source in Cement Kilns: Investigation of Optimum Feeding Rate

Abstract: Abstract. Meat and Bone Meal (MBM) is a CO 2 neutral fuel, and hence is a good candidate for substituing fossil fuels like pulverized coal in rotary kiln burners used in cement kiln systems. MBM is used in several cement plants, but the optimum substitution rate has apparently not yet been fully investigated. The present study aims to find the maximum possible replacement of coal by MBM, without negatively affecting the product quality, emissions and overall operation of the process. A full-scale experiment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…2) Quantification of the reduction of production capacity due to replacement of more than half of the primary coal energy by MBM using an expanded model, which also included the precalciner (required for the total mass balance of the system). The simulation results were verified by results from a full-scale test partly documented before [12]. A description of the kiln system is described in a previous publication [13].…”
Section: Introductionmentioning
confidence: 62%
“…2) Quantification of the reduction of production capacity due to replacement of more than half of the primary coal energy by MBM using an expanded model, which also included the precalciner (required for the total mass balance of the system). The simulation results were verified by results from a full-scale test partly documented before [12]. A description of the kiln system is described in a previous publication [13].…”
Section: Introductionmentioning
confidence: 62%
“…Thus, one should expect a decreasing temperature after the maximum point [19]. The fact that burning MBM in higher rates reduces the flame temperature and hence heat transfer in the kiln has been verified by a full-scale experiment and published in another paper [43]. Having a high volatiles content compared to coal (Table I), MBM shows intense devolatilization nearby the burner, and it also extends a longer into the kiln (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Hence, the fuel replacement ratio corresponding to this point, about 58 %, could be taken as a maximum value which should not be exceeded, from a char burnout point of view. In a full-scale experiment carried out with a mixture of coal and MBM, it was found that there is an issue related to product quality when the replacement ratio exceeds about 50% [9], which was basically explained by a negative impact of reduced temperature. In the present study, it was found that the replacement ratio should be kept below about 58% in order to get maximum advantages of fuel replacement with respect to fuel char burnout point.…”
Section: B Correlation Of Fuel Replacement Ratio With Equilibrium Gamentioning
confidence: 99%
“…In a previous modeling study carried out by the authors of the current study, it was found that the kiln gas flow rate is higher and the kiln gas temperature is lower for MBM than for several other solid waste-derived fuels, when replacing 100% of the coal energy in the cement rotary kiln [3], [8]. A full-scale cement kiln test also demonstrated the negative effects of burning high amounts of MBM [9]. Moreover, the authors of the current study used CFD to carry out simulations of MBM combustion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation